Dolus Specialis Dalam Pembuktian Genosida: Tantangan Penegakan Hukum Internasional - Muthmainnah, Aisyah; Ferdi, Ferdi; Syofyan, Syofirman (Lareh Law Review, 2024)
Genocide as the most serious crime is specifically regulated in international law. The regulation of genocide is contained in the Convention on the Prevention and Punishment of the Crime of Genocide 1949. Specific intent or dolus specialis is the main element in proving genocide. This special intention distinguishes genocide from other crimes. However, the existence of this special intent is often a source of controversy in international law enforcement practice. The lack of clarity in defining and proving special intent often causes difficulties in the judicial process, and can result in injustice for victims. This article discusses two problem formulations, firstly how the concept of dolus specialis is applied in proving the crime of genocide and secondly how the law enforcement of acts of genocide in the perspective of international law. This article uses normative juridical method. The results of this study show that special intent focuses on the perpetrator's intention to destroy a particular group, for example a statement by a high-ranking official indicating an intention to commit genocide, but in practice this is difficult to prove. Law enforcement against acts of genocide can be held accountable to the state and individuals concerned. Keywords : Keywords : Genocide, Intent, International Law Enforcement